Application of brassinolide mitigates saline stress of certain metabolites of sorghum grown in Karaikal - Vardhini, B Vidya (Journal of Phytology, 2012)
Effect of brassinolide on the metabolite contents (free proline, soluble proteins and RNA) of two sorghum varieties (‘CSH-5’ and ‘CSH-6’) grown in two saline experimental sites of Karaikal viz. Varchikudy and Mallavur, was studied. Brassinolide application resulted in substantial elevated levels of free proline, soluble proteins and RNA of the two varieties of sorghum plants grown in two saline experimental sites of Karaikal. The study revealed that brassinolide was more effective in more saline site –II (Mallavur) than less saline site –I (Varchikudy) thus indicating its ability to counteract the negative impact of saline stress.